Competitve Growth: the Development of Key Competences and Corporate Venturing - A. I. Kashirin; V. V. Strenalyuk; A. S. Semennov; A. A. Ostrovskaya; T. V. Kokuytseva (Управленческие науки, 2016)
The article is based on the hypothesis that formation, keeping and development of organization’s key competences each reflecting the competitive advantage is the most important condition for business’ competitive growth. With scientific and technical acceleration, formation of new highly technological and dynamically developing branches, such as information, nano- and bio-technologies, new ways of creating and implementing innovations are emerging also. The modern ways of managing them including technologies transfer, venture investment, open innovations system and key competences are becoming not less important. The corporate venture investment is the effective synthesis of two approaches. Methodic complexity of emphasizing and weak working out the procedures of competences’ formation, development and management and besides the Russian companies’ managers do not have any working skills with competences lead to the fact that this important asset is not practically used. Many domestic companies possess such competences but they are not described, not systemized, there is no management by them. The present work is aimed at the investigation of such mechanisms of forming the sustainable competitive advantages under modern conditions as the development of enterprise’s unique technological competences and the application of corporate venturing elements as well.